(untitled) (Research, Society and Development, 2021)
Objective: to describe the professional relationship of the social actors of the Multiprofessional Residency in Health (RMS) with the nurse-preceptor. Methodology: qualitative, descriptive and exploratory research, of the type of single case study. The scenario was the São Francisco de Assis Health Care Institute of the Federal University of Rio de Janeiro (HESFA / UFRJ) which has two RMS Programs: Women’s Health (RMS-SM) and Family and Community Health (RMS-SFC). The data were produced through interviews, observation and document analysis. 46 professionals participated in the study. The study was approved by the Research Ethics Committee of the Anna Nery School of Nursing / HESFA / UFRJ under the number of Opinion: 776.075 it’s from CAAE: 34835714.0.0000.5238. Results: The activities that tutors, teachers, preceptors, coordinators and residents (social actors) developed with the nurse-preceptor were different, aiming mainly at guaranteeing the functioning of the programs. The social actors described their professional relationship in the residence with the nurse-preceptor, with greater or lesser approximation, depending on the role they played. Conclusion: The importance of building collective and collaborative work for effective changes in the practices of health scenarios is highlighted, strengthening the inter-professional bonds between all the protagonists of the RMS.